Conditions and access to health services for quilombola women and children: an integrative review (Research, Society and Development, 2022)
Objective: To identify scientific evidence about the health conditions and access to health services of quilombola women and children. Methods: Integrative literature review carried out in the following databases: PUBMED, SciELO, LILACS and CINAHL. Results: A total of 1,714 records were evaluated in title and abstract. After careful reading and application of inclusion and exclusion criteria, 23 articles were selected for analysis. It was found that most of the selected publications were from the LILACS database, with 13 manuscripts, followed by CINAHL with 4 articles. Three articles were from SciELO and three from PubMed, all from Brazil, in Portuguese, English and Spanish, except for 2 articles only in English. The year of publication of the articles varied between 2013 and 2021. The findings showed precarious health conditions and difficulties in accessing health services, with the location of the quilombola community being a limiting factor, which causes numerous challenges, such as difficult access to health services and their precariousness. Conclusion: The results evidenced in this study were important to understand the health issues of this vulnerable group, raising reflections for health professionals, society and public policy makers about the importance of promoting greater access and better quality to women's and children's health of the quilombola population.